Acceso a redes inalámbricas de la ESPAM MFL mediante un servidor radius - Loor Anchundia, José Rubén (2019)
The present investigation is about the implementation of a RADIUS server in Sector 8 at ESPAM MFL, against the current problem that could be observed from a social - organizational context the breach of policies, procedures and processes for the control of the access of the networks the implementation of mechanisms for their management and administration. For the development we used the EDER methodology (study, design, execution and review), which clearly defines the processes and procedures for the application of technological infrastructure projects, the method used for sampling was directed. In order to gather the information, interviews were carried out with the staff of the Technology Unit and surveys of the users of the institution (teachers, administrative staff and students), which allowed to know the current situation of the wireless networks. The Acrylac Wi-Fi Home Software and Acrylac Wi-Fi HeadMaps 4.1 were used to monitor and characterize the wireless networks and access points. Oracle VM Virtual Box 6.0, CentOS 7, daloRADIUS 1.0-0 among other programs were installed; the wireless access equipment configurations and the respective tests for the RADIUS server implementation were performed. The main results of the research on the way of access to wireless networks and academic and non-academic resources and the perception of the level of security of institutional information that users have are shown; and finally the discussion, conclusions and recommendations are presented.